Simultaneous detection of Ca2+ and diacylglycerol signaling in living cells. - Paul Tewson; Mara Westenberg; Yongxin Zhao; Robert E Campbell; Anne Marie Quinn; Thomas E Hughes (PLoS ONE)
Phospholipase C produces two second messengers--diacylglycerol (DAG), which remains in the membrane, and inositol triphosphate (IP(3)), which triggers the release of calcium ions (Ca(2+)) from intracellular stores. Genetically encoded sensors based on a single circularly permuted fluorescent protein (FP) are robust tools for studying intracellular Ca(2+) dynamics. We have developed a robust sensor for DAG based on a circularly permuted green FP that can be co-imaged with the red fluorescent Ca(2+) sensor R-GECO for simultaneous measurement of both second messengers.